Kinetics of coagulation in ST-elevation myocardial infarction following successful primary percutaneous coronary intervention. (January 2016) - Teunissen, Paul F.A.; Tijssen, Ruben; van Montfoort, Maurits L.; Robbers, Lourens F.H.J.; de Waard, Guus A.; van de Ven, Peter M.; Beek, Aernout M.; Knaapen, Paul; Meijers, Joost C.M.; van Royen, Niels
Abstract: Introduction: ST-elevated myocardial infarction (STEMI) is most frequently caused by coronary occlusion due to formation of an intracoronary thrombus in reaction to rupture of atherosclerotic plaques. Little is known about kinetics of coagulation markers after STEMI in patients treated according to current guidelines. We aimed to investigate kinetics of important coagulation markers in percutaneous coronary intervention (PCI)-treated STEMI patients. Materials and methods: 60 consecutive PCI-treated STEMI patients were prospectively included. Blood samples were collected immediately after as well as 1, 4 and 7 days following PCI. Samples collected 90 days after PCI served as baseline values. ADAMTS13 activity, VWF (von Willebrand factor) activity, VWF antigen, VWF propeptide, fibrinogen antigen, D-dimer, alpha2-antiplasmin (α2AP), plasmin-alpha2-antiplasmin complex (PAP), prothrombin fragment F1 + 2 (F1 + 2), prothrombin time (PT), activated partial thromboplastin time (aPTT), and anti-factor Xa (anti-Xa) were measured. Cardiac magnetic resonance (CMR) was performed at 4–6 and 90 days after PCI in 49 patients and left ventricular ejection fraction (LVEF), infarct size and microvascular injury (MVI) were determined. Results: Immediately after PCI, ADAMTS13 activity, fibrinogen antigen and α2AP levels were significantly decreased and VWF activity, VWF antigen and VWF propeptide levels were significantly elevated, compared to baseline. Individual coagulation markers and different combinations thereof were not related to LVEF or infarct size at 90 days, or the occurrence of MVI at 4–6 days after PCI. Conclusion: Coagulation parameters show a very dynamic profile in the early days after STEMI. However, individual coagulation parameters or combinations thereof do not predict CMR-defined LVEF, infarct size or MVI. Highlights: Coagulation parameters show a very dynamic profile in the early days after ST-elevation myocardial infarction. Individual coagulation parameters do not predict CMR-defined LVEF, infarct size or microvascular injury (MVI). Combinations of coagulation parameters do not predict CMR-defined LVEF, infarct size or MVI.